2010
DOI: 10.1186/cc9348
|View full text |Cite
|
Sign up to set email alerts
|

No agreement of mixed venous and central venous saturation in sepsis, independent of sepsis origin

Abstract: IntroductionControversy remains regarding the relationship between central venous saturation (ScvO2) and mixed venous saturation (SvO2) and their use and interchangeability in patients with sepsis or septic shock. We tested the hypothesis that ScvO2 does not reliably predict SvO2 in sepsis. Additionally we looked at the influence of the source (splanchnic or non-splanchnic) of sepsis on this relationship.MethodsIn this prospective observational two-center study we concurrently determined ScvO2 and SvO2 in a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 24 publications
2
25
0
1
Order By: Relevance
“…The wide limits of agreement across all comparisons between ScvO 2 and SvO 2 observed in our study parallel those seen in other publications [18,20,21] and reinforce the notion of a modest mutual association.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The wide limits of agreement across all comparisons between ScvO 2 and SvO 2 observed in our study parallel those seen in other publications [18,20,21] and reinforce the notion of a modest mutual association.…”
Section: Discussionsupporting
confidence: 80%
“…Our data is in line with similar observations in diverse clinical settings [8,17,18,19]. We also specifically investigated the impact of the underlying hemodynamic status on the interchangeability of ScvO 2 and SvO 2 by dichotomizing patients based on a cardiac index cut-off point of 2.0 L/min/m 2 .…”
Section: Discussionsupporting
confidence: 58%
“…[20], this included critically ill ICU patients [21], and during liver transplantation [22]. On the other hand, other studies presented an unacceptable agreement between both measurements [4,5,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…There has been considerable debate regarding whether ScvO 2 is a satisfactory substitute for SvO 2 . The previous studies evaluating the relationship between ScvO 2 and SvO 2 showed a significant variation in results because of different study designs and clinical setup which included intensive care patients with either sepsis, heart failure, or shock [4][5][6][7]. Studies involving such relationship during and after cardiac surgery [8][9][10][11][12][13][14][15] also showed contradicting results, this controversy is generating confusion among clinicians and further work is needed to explore this area.…”
Section: Introductionmentioning
confidence: 92%
“…However, recent clinical trials, involving mainly septic patients, were unable to show satisfactory agreement between ScvO 2 and SvO 2 . This could in part be explained by modifications of blood flow distribution and oxygen extraction by brain and splanchnic tissues [31].…”
Section: Parameters Reflecting Vomentioning
confidence: 99%